A multi-center clinical investigation on invasive Streptococcus pyogenes infection in China, 2010-2017 - Chun-Zhen Hua; Hui Yu; Hong-Mei Xu; Lin-Hai Yang; Ai-Wei Lin; Qin Lyu; Hong-Ping Lu; Zhi-Wei Xu; Wei Gao; Xue-jun Chen; Chuan-Qing Wang; Chun-mei Jing (BMC, 2019)
Abstract Background Invasive S. pyogenes diseases are uncommon, serious infections with high case fatality rates (CFR). There are few publications on this subject in the field of pediatrics. This study aimed at characterizing clinical and laboratory aspects of this disease in Chinese children. Patients and methods A retrospective study was conducted and pediatric in-patients with S. pyogenes infection identified by cultures from normally sterile sites were included, who were diagnosed and treated in 9 tertiary hospitals during 2010-2017. Results A total of 66 cases were identified, in which 37 (56.1%) were male. The median age of these patients, including 11 neonates, was 3.0 y. Fifty-nine (89.4%) isolates were determined from blood. Fever was the major symptom (60/66, 90.9%) and sepsis was the most frequent presentation (64/66, 97.0%, including 42.4% with skin or soft tissue infections and 25.8% with pneumonia. The mean duration of the chief complaint was (3.8 ± 3.2) d. Only 18 (27.3%) patients had been given antibiotics prior to the hospitalization. Among all patients, 15 (22.7%) developed streptococcal toxin shock syndrome (STSS). No S. pyogenes strain was resistant to penicillin, ceftriaxone, or vancomycin, while 88.9% (56/63) and 81.4% (48/59) of the tested isolates were resistant to clindamycin and erythromycin respectively. Most of the patients were treated with β-lactams antibiotics and 36.4% had been treated with meropenem or imipenem. Thirteen (19.7%) cases died from infection, in which 9 (13.6%) had complication with STSS. Conclusions Invasive S. pyogenes infections often developed from skin or soft tissue infection and STSS was the main cause of death in Chinese children. Ongoing surveillance is required to gain a greater understanding of this disease.